FRACTURE ANALYSIS AND IMPROVEMENT OF EGR COOLER WITH ECCENTRIC INTAKE STRUCTURE - HONG Yang; ZHENG ShiQian; SHEN HaiQing; ZHAO GuoJiang (Jixie qiangdu)
Aiming at welding fracture problem of EGR cooler with eccentric intake structure,numerical simulation based on sequential fluid-solid coupling was presented and the improvement of eccentric intake structure was taken. Flow field mesh and solid finite element mesh were set up based on 3 D modeling. The sequential fluid-solid coupling with flow field analysis,heat conduction analysis and thermal stress analysis was taken to study the relation among intake structure,gas side streamline,solid temperature,thermal stress range and the fracture. An improvement scheme with increasing a hump was proposed to improve gas uniformity and reduce local thermal stress range. The results indicate that the sequential fluid-solid coupling is feasible in engineering practice,the partial fracture of EGR cooler will caused by unreasonable eccentric intake structure and will be solved by optimization of flow passage.